The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008 9th International Workshop and Tutorials on Electron Devices and Materials 2008
DOI: 10.1109/sibedm.2008.4585902
|View full text |Cite
|
Sign up to set email alerts
|

The ultrasonic flowing reactor for intensive ultrasonic processing of liquids in thin layer

Abstract: In article the information about the ultrasonic flowing reactor allowing manufacture of highintensity cavitations processing of liquid and liquiddispersed mediums in a thin layer is presented. Such method considerably increases the efficiency and productivity of processing that let use it in industrial conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is demonstrated that all of these processes can be carried out efficiently only by initiating and maintaining a cavitation process in liquid (in phase of "stable cavitation"). Cavity bubbles generated in a liquid or a liquid dispersed media have the most energy effect on the surrounding liquid during the bubble collapse phase (Abramenko et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that all of these processes can be carried out efficiently only by initiating and maintaining a cavitation process in liquid (in phase of "stable cavitation"). Cavity bubbles generated in a liquid or a liquid dispersed media have the most energy effect on the surrounding liquid during the bubble collapse phase (Abramenko et al, 2008).…”
Section: Introductionmentioning
confidence: 99%